The Interplay Between Global Digital Trade and Data Privacy Policy: A Comprehensive Review - Sun, Yijing (Transactions on Economics, Business and Management Research, 2024)
In the era of big data, international trade has gone through a digital transformation and developed into a new stage of digital trade. The gradual prosperity of digital trade and the increasing contribution of digital elements to the economy of countries and the international community also bring about problems such as data abuse, surveillance, privacy infringement, and regulatory difficulties. In order to adapt to the development trend of digital trade, countries are paying more attention to cross-border data flow and data privacy protection, in order to maintain national security and the data security of various entities. Therefore, this article analyzes the current situation and trends of digital trade, considers the security issues of data privacy from the perspective of different entities, links key issues such as cross-border data flow, data rights, and privacy rights, explores the current status of relevant domestic and foreign legal and regulatory systems, and conducts comparative analysis. The analysis results show that due to different values, there are significant differences in policies regarding digital trade and privacy protection among countries. The commonality is that none of them have established appropriate legal protection systems for data elements and privacy rights to promote the development of digital trade. Under the trend of technological development, data privacy will also be impacted by new technologies through digital trade. Therefore, in response to the expanding demand for data regulation, all entities should improve their privacy protection and cross-border data flow policies and standards from both internal and international perspectives.